Competitiveness of Smallholder Beef Cattle Farming in Gorontalo District, Gorontalo - ari abdul rouf; Arief Daryanto; Anna Fariyanti (Buletin Peternakan, 2019)
The objectives of this study were to analyze the competitiveness of the beef cattle farming in Gorontalo District, to analyze the impact of government policies on competitiveness and to analyze the impact of changes in input and output factors of production to competitiveness. Primary data were obtained from 60 respondents were selected using non-probability sampling method. The analysis methods used were Policy Analysis Matrix (PAM) and sensitivity analysis. The results of the analysis showed that the commodity beef cattle in Gorontalo District has a weak competitiveness. The impact of policy to the beef cattle farming showed that the farmers are not protected by government policies (EPC<1). The impact of changes in input and output of production on the competitiveness showed that: 1) the increase in the price of domestic meat and the world respectively 8.44%  and 10% will increase the competitiveness, 2) an increase in the price of feeder cattle at 3.28%, forage feed costs by 10% and labor costs by 10% will impact beef cattle farming do not have a competitive advantage but still have a comparative advantage, and 3) increase in meat production about 12.72% will increase the competitiveness of beef cattle.